PARADIGMA HUKUM RESPONSIF (Suatu kajian tentang Makamah Konstitusi sebagai Lembaga Penegak Hukum) - Muchtar, Henni (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
It is really ironic that an institution of law enforcer like constitutional court whose objectives are to to defend the rights, create substantive justice and prosperity for the society, is apparently extending its authority—including constitutional complain toward the static Supreme Court’s decision—which causes concern among the society. People are worried about the lack of control of the extension on authority, indicating it will become the highest institution with no check and balances as well as the fear of increasing debates and problems among the society. This article suggests that constitutional court can explain the consideration of extending the authority to the public, in order to counter the public’s anxiousness that the institution is becoming the highest authority without check and balances.Key words: extension of authority, constitutional court, constitutional complain, society rights, Supreme Court